Comparative Spectral Sensitivity and Quantitative Accuracy of X-ray Fluorescence and Optical Emission Spectroscopy for Alloy Steel Characterization - Kazimierz Nowaczyk; Risky Hidayat Santoso Putra; Piroska Pataki (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to evaluate and compare the spectral sensitivity, detection capability, and quantitative accuracy of X-ray fluorescence and optical emission spectroscopy in determining the elemental composition of alloy steel. Methodology: X-ray fluorescence analysis was conducted using Niton XL2 GOLDD (Thermo Scientific), while optical emission spectroscopy analysis employed ARC Met 8000 (Oxford Instruments). Samples included stainless steel (SS-304, SS-310), alloy steel (17-4PH), and duplex steel (Zeron 100). Calibration was performed using Analytical Reference Materials International standards. Data analysis included averaging repeated measurements, relative error calculation, and comparative evaluation using Microsoft Excel and Origin software. Main Findings: Optical emission spectroscopy demonstrated higher spectral sensitivity, particularly for light elements such as carbon, while X-ray fluorescence provided rapid multi-element detection with acceptable accuracy. Relative deviations between methods varied across elements, with significant discrepancies observed in nickel measurements due to matrix effects and detection limitations. Novelty/Originality of this study: This study introduces a comparative spectral performance analysis of X-ray fluorescence and optical emission spectroscopy, emphasizing matrix-effect-driven deviations and highlighting the nickel (Ni) anomaly as a key spectroscopic case. The work provides deeper insight into the influence of spectral interactions on analytical accuracy in complex alloy systems.